BOLD cerebrovascular reactivity as a novel marker for crossed cerebellar diaschisis. (2nd October 2018) - Sebök, Martina; van Niftrik, Christiaan H.B.; Piccirelli, Marco; Bozinov, Oliver; Wegener, Susanne; Esposito, Giuseppe; Pangalu, Athina; Valavanis, Antonios; Buck, Alfred; Luft, Andreas R.; Regli, Luca; Fierstra, Jorn
Abstract : Objective: To study blood oxygen level–dependent cerebrovascular reactivity (BOLD-CVR) as a surrogate imaging marker for crossed cerebellar diaschisis (CCD). Methods: Twenty-five participants with symptomatic unilateral cerebrovascular steno-occlusive disease underwent a BOLD-CVR and an acetazolamide challenged ( 15 O)-H2 O-PET study. CCD and cerebellar asymmetry index were determined from PET and compared to BOLD-CVR quantitative values. Neurologic status at admission and outcome after 3 months were determined with NIH Stroke Scale (NIHSS) and modified Rankin Scale (mRS) scores. Results: For both the BOLD-CVR and PET examination, a significant cerebellar asymmetry index was found for participants exhibiting CCD (CCD+ vs CCD−: for BOLD-CVR 13.11 ± 9.46 vs 1.52 ± 4.97, p < 0.001; and for PET 7.31 ± 2.75 vs 1.68 ± 2.98, p < 0.001). The area under the curve for BOLD-CVR was 0.89 (95% confidence interval: 0.75–1.0) with 0.91 sensitivity and 0.81 specificity to detect CCD. Participants exhibiting CCD were in poorer clinical condition at baseline (CCD+ vs CCD−: NIHSS 7 vs 1, p = 0.003; mRS 3 vs 1, p = 0.001) and after 3-month follow-up (NIHSS 2 vs 0, p = 0.02; mRS 1 vs 0, p = 0.04). Worse performance on both scores showed an agreement with a larger BOLD-CVR cerebellar asymmetry index. This was not found for PET. Conclusions: BOLD-CVR demonstrates similar sensitivity to detect CCD as compared to ( 15 O)-H2 O-PET in patients with symptomatic unilateral cerebrovascular steno-occlusive disease. Furthermore, participants exhibiting CCD had a poorer baseline neurologic performance and neurologic outcome at 3 months. Classification of evidence: This study provides Class II evidence that BOLD-CVR identifies CCD in patients with symptomatic unilateral cerebrovascular steno-occlusive disease.